A quantitative analysis of determinants of child and maternal malnutrition in Nigeria - Ajieroh, Victor (International Food Policy Research Institute, 2010)
Malnutrition rates among children 0 to 36 months and women of reproductive age in Nigeria are high and vary significantly across rural urban locations, geopolitical zones, and agro-ecological zones, thereby constituting a significant public health challenge. Using the 2003 National Demographic Health Survey (NDHS) data, this brief discusses the key determinants of child and maternal nutrition in Nigeria across these different zones.